The profitability of Malaysian’s listed manufacturing companies / Muhammad Naqiuddin Nadzari - Nadzari, Muhammad Naqiuddin (2015)
Profitability of manufacturing company can be measure based on the financial performance. A better profit were determine better firm. The research about profitability of Malaysian’s listed manufacturing companies were conduct to reveal the factors that influence firm performance. The main objective of this study is to investigate the relationship between independent variables with dependent variable of return on assets of manufacture sector in Malaysia based on financial ratio at the year 2005 until 2014 with mean profitability (return on assets) as dependent variable meanwhile efficiency (total assets turnover), leverage (debt ratio), liquidity (current ratio) and firm size as an independent variable. The number of companies was taken 70 listed companies which have complete data in 10 years from Osiris. Then the total of all data come out with 700 and this research based on secondary data. The data were analyzed using StatalO through Static Panel Data analysis and tested using Ordinary Least Square Regression (OLS), Random Effect Generalized Least Square Regression (GLS), (Breusch and Pagan Test) and Fixed Effect (Hausman Fixed Test). From the result of the study come out liquidity, leverage and efficiency are positively significant to profitability. However, size of firm is insignificant to profitability.